Host genetic influence on papilloma virus-induced tumors in the Horse - Staiger EA; Tseng CT; Miller D; Cassano J; Nasir L; Garrick DJ; Brooks SA; Antczak DF (John Wiley & Sons)
The common equine skin tumors known as sarcoids have been causally associated with infection by bovine papillomavirus (BPV). Additionally, there is evidence for host genetic susceptibility to sarcoids. We investigated the genetic basis of susceptibility to sarcoid tumors on a cohort of 82 affected horses and 270 controls genotyped on a genome-wide platform and two custom panels. A Genome Wide Association Study (GWAS) identified candidate regions on six chromosomes. Bayesian probability analysis of the same dataset verified only the regions on equine chromosomes (ECA) 20 and 22. Fine mapping using custom-produced SNP arrays for ECA20 and ECA22 regions identified two marker loci with high levels of significance: SNP BIEC2-530826 (map position 32,787,619) on ECA20 in an intron of the DQA1 gene in the Major Histocompatibility Complex (MHC) class II region (p = 4.6e-06), and SNP BIEC2-589604 (map position 25,951,536) on ECA22 in a 200 kb region containing four candidate genes: PROCR, EDEM2, EIF6 and MMP24 (p = 2.14e-06). The marker loci yielded odds ratios of 5.05 and 4.02 for ECA20 and ECA22, respectively. Associations between genetic MHC class II variants and papillomavirus-induced tumors have been reported for human papillomavirus and cottontail rabbit papillomavirus infections. This suggests a common mechanism for susceptibility to tumor progression that may involve subversion of the host immune response. This study also identified a genomic region other than MHC that influenced papillomavirus-induced tumor development in the studied population.
Keywords: papillomavirus; sarcoid tumor; horse; MHC; GWAS; 1112 Oncology and Carcinogenesis